Comparison of the nutritive value of soybean meal from U.S. and Brazilian soybeans - Zhang, Xuyan (Kansas State University, 2021)
What are the differences of soybean meal produced from different countries’ soybeans? The U.S. soybean industry strives to differentiate U.S. soybeans in the Chinese domestic market for the livestock and aquaculture industry. More than 90% of China’s soybean consumption is dependent on imported soybeans. More than 60% of U.S. soybean exports enter the Chinese market. The U.S. and Brazil are the top two soybean sellers to the Chinese market. The Brazilian soybean share in Chinese market increased in the past several years due to U.S.-China trade disputes. The U.S. soybean industry goal is to expand their sales volume in China and differentiate the U.S. soybean from those produced in other countries. In this study twenty-three Brazil soybean meal samples and twenty-seven U.S. soybean meal samples were analyzed and the nutrient value was compared. Wet chemistry methods were used to test the major amino acids profile in soybean meal. Results showed that five amino acids from the U.S. beans are greater than Brazil, but not statistically significant. The sucrose and stachyose levels from the U.S. beans are statistically greater than Brazil. Digestibility of dry matter and crude protein from U.S. soybean meal are not statistically significantly greater than Brazilian soybean meal. The quality of U.S. origin soybean meal is greater than Brazil. With the price of 43% protein level being the same in China, soybean meal end users, livestock producers will benefit from using U.S. originated soybean meal.
Keywords: Soybeans; China; Brazil; United States; Agribusiness